Bài làm:
#Tìm Max của biểu thức:
\(A=\frac{3-4x}{x^2+1}=\frac{4\left(x^2+1\right)-\left(4x^2+4x+1\right)}{x^2+1}=4-\frac{\left(2x+1\right)^2}{x^2+1}\)
Mà \(\hept{\begin{cases}\left(2x+1\right)^2\ge0\\x^2+1>0\end{cases}\left(\forall x\right)\Rightarrow}-\frac{\left(2x+1\right)^2}{x^2+1}\le0\left(\forall x\right)\)
\(\Rightarrow A\le4\left(\forall x\right)\)
Dấu "=" xảy ra khi: \(\left(2x+1\right)^2=0\Rightarrow x=-\frac{1}{2}\)
Vậy \(Max\left(A\right)=4\Leftrightarrow x=-\frac{1}{2}\)
#Tìm Max và Min của B:
Tìm Min
\(B=\frac{2x}{x^2+1}=\frac{\left(x^2+2x+1\right)-\left(x^2+1\right)}{x^2+1}=\frac{\left(x+1\right)^2}{x^2+1}-1\)
Mà \(\hept{\begin{cases}\left(x+1\right)^2\ge0\\x^2+1>0\end{cases}\left(\forall x\right)\Rightarrow}\frac{\left(x+1\right)^2}{x^2+1}\ge0\left(\forall x\right)\)
\(\Rightarrow B\ge-1\left(\forall x\right)\)
Dấu "=" xảy ra khi: \(\left(x+1\right)^2\ge0\Rightarrow x=-1\)
Vậy \(Min\left(B\right)=-1\Leftrightarrow x=-1\)
Tìm Max
\(B=\frac{2x}{x^2+1}=\frac{x^2+1-\left(x^2-2x+1\right)}{x^2+1}=1-\frac{\left(x-1\right)^2}{x^2+1}\)
Mà \(\hept{\begin{cases}\left(x-1\right)^2\ge0\\x^2+1>0\end{cases}}\left(\forall x\right)\Rightarrow-\frac{\left(x-1\right)^2}{x^2+1}\le0\left(\forall x\right)\)
\(\Rightarrow B\le1\left(\forall x\right)\)
Dấu "=" xảy ra khi: \(\left(x-1\right)^2=0\Rightarrow x=1\)
Vậy \(Max\left(B\right)=1\Leftrightarrow x=1\)
Sao dạo này nhìu bạn đăng mấy câu như vậy lên thế nhỉ?